Chronic Pain in Autistic Youth: Clinical Prevalence and Reflections on Tailoring Evidence-Based Interventions from an Interdisciplinary Treatment Team - Gloria T. Han; Holly S. Heavner; Thomas R. Rains; Alan H. Hoang; Amanda L. Stone (MDPI AG, 2024)
Though there is growing awareness of the overrepresentation of autistic patients in chronic pain clinics, potential adaptations for the assessment and treatment of chronic pain in this population have not yet been established. To address this gap, a retrospective review of electronic medical records and discussions by an interdisciplinary pain treatment team were summarized to inform potential biopsychosocial factors affecting the presentation, assessment, and treatment of chronic pain in autistic youth. Our sample included a record review of 95 patients receiving treatment in an interdisciplinary outpatient pediatric pain clinic. Results indicated that 9% (n = 9) of the patients presented to the clinic with a prior diagnosis of autism, but an additional 21% (n = 20) were identified as likely meeting criteria for autism based on the clinical assessment of the developmental history, behaviors observed during the clinical encounter(s), and expert clinical judgment, suggesting that the prevalence rate of autism may be closer to 30% in our outpatient pediatric pain clinic. Over half (52%) of the autistic youth presented to the clinic with widespread pain, 60% identified as female, and 6% identified as gender expansive or transgender. Qualitative insights revealed that most of the autistic patients had co-occurring sensory-processing challenges and difficulty in describing their pain, emotions, and somatic experiences and exhibited cognitive inflexibility and social challenges. We summarize our team's clinical reflections on how autism-relevant biopsychosocial vulnerability factors may contribute to the experience of pain in autistic youth and propose treatment targets and adaptations for the assessment and treatment of pain in this population. Finally, we recommend the need for interventions focused on sensorimotor integration, especially for autistic youth, and describe how pain clinics may be particularly helpful for identifying and supporting autistic females, for whom the potential role of autism in pain experiences had not been considered until receiving treatment in our clinic.